Study the Preparation of Polymeric Coatings Supported by Nanomaterials to Inhibit Corrosion in the Oil Tanks - Jasim, Omar A.; Al-Sarraf, Abdulhameed Raheem (Journal of Petroleum Research and Studies, 2020)
In order to determine the most suitable composite coatings to inhibit corrosion in the oil tanks, the protection method was studied by the method of multiple layers of protection. Where there were three layers of protection, the base layer is a phosphate process using zinc phosphate, the second layer is a base painting (Hydrazine Hydrate with an epoxy zinc coating), while the top layer was a composite coating matrix of unsaturated polyester and epoxy supported by different fraction weight of nanomaterials. The top layer was supported by nano kaolin with 1% weight fraction, nano magnesium oxide with 3% weight fraction and nano zinc oxide with 5% weight fraction. The three layers were painted on metal pieces (1.5cm*1.5cm) of corroded tanks used to store diesel fuel. The hardness of the metal parts was studied before and after the phosphate process, where the results showed that the sample surface hardness was 123 HB and after the phosphate process was 131 HB. The chemical corrosion and electrochemical corrosion test were carried out for a group of samples that were painted only once with a topcoat and again with three layers of paint. The results showed that the best protection against corrosion is the sample that painted with three layers of coating, and the top coating supported by a nano magnesium oxide, it has lowest corrosion current value (162.59 nA/cm2). Furthermore, the adhesion test showed that the coating supported by nanomaterials have higher adhesion strength than those that are not supported by nanomaterials. Where the highest adhesion strength was (776 Psi) for magnesium oxide nanoparticle coating.